4 KEGIATAN KEAGAMAAN SMP MUHAMMDIYAH BATU: MAMPU MEMPENGARUHI AKHLAK PESERTA DIDIK? - Isnawardatul Bararah (Jurnal Mudarrisuna: Media Kajian Pendidikan Agama Islam, 2021)
This study aims to determine the level of influence of each of the 4 religious activities (jamaah prayer, morning tadarus, friday infaq, and dhuha prayer) on the morals of students, using an associative quantitative research approach. This study used a sample of 77 from a total population of 342 students at SMP Muhammadiyah 8 Batu, with data collection techniques using a 5 variable questionnaire, namely jamaah prayer, morning tadarus, friday infaq, dhuha prayer (4 religious activities) and morals students with a random sampling system. To analyze the data, researchers used the product moment correlation and the coefficient of determination. The results of this study indicate that each of the 4 religious activities has a different level of influence on the morals of students, including jamaah prayer has an effect of 0.358 (low); morning tadarus has an effect of 0.1744 (low); friday infaq has an effect of 0.5418 (medium); dhuha prayer has an effect of 0.012 (medium); with an overall average of 93.9, which means that the effect value is sufficient, so that the 4 religious activities can affect the morals of students at SMP Muhammadiyah 8 Batu with rcount 0.706> rtable 0.227, with the influence of 57.76% is significant effect.